A Canadian Perspective on Japanese-English Language Contact - Yoshizumi, Yukiko (Université d'Ottawa / University of Ottawa, 2016)
This dissertation investigates the linguistic outcomes of Japanese-English language contact in Canada. Adopting a sociolinguistic variationist framework (Labov 1966; Sankoff & Labov 1985), the main objective is to determine whether or not Japanese spoken in Canada (hereafter, heritage Japanese) is showing structural change due to prolonged contact with English. The study is based on naturalistic speech data collected from 16 Japanese-English bilingual speakers in Canada. A key component of this dissertation is the use of a comparative sociolinguistic framework (Poplack and Tagliamonte 2001; Tagliamonte 2002) to assess structural affinities between heritage Japanese and the homeland Japanese benchmark variety. Speech patterns in heritage Japanese are systematically compared with patterns found in a commensurate monolingual benchmark variety of Japanese with regard to three linguistic variables, which are considered to be vulnerable to contact-induced language change (i.e. Bullock 2004, Sorace 2011). In terms of the first variable analyzed, variable realization of subject pronouns, it was found that the underlying grammar in heritage Japanese is shared by the homeland benchmark variety, showing that the variable is conditioned by the factor groups of subject continuity (i.e. switch reference) and grammatical person; the null variant is favoured by the same subject referent and the second person pronoun. Second, with regard to variable case marking on subject nouns and variable case marking on direct object nouns, it was found that the same underlying grammar is shared for case marking. For example, the constraint hierarchies in heritage Japanese were identical with those in the homeland variety for focus particles, with presence of a focus particle favouring null marking consistently for all types of nouns (i.e. English-origin nouns and Japanese nouns in heritage Japanese, and Japanese nouns and loanwords in homeland Japanese). The constraint hierarchies (and direction of the effect) for the other significant factor groups of verbal adjacency and sentence-final particle were identical between heritage Japanese and the homeland variety, with the exception of a reversed direction of effect for loanword subject nouns in heritage Japanese for the non-significant factor group of verbal adjacency, and a neutralized effect for Japanese nouns in heritage Japanese and loanwords in homeland Japanese when these nouns are located in direct object position. Considered in the aggregate, constraint hierarchies were found to exhibit a number of parallels across comparison varieties. This finding bolsters the general conclusion that there is little evidence indicating that extensive contact with English has had any discernible impact on structural patterns in these sectors of the heritage grammar. Furthermore, it was shown that no social factor group (i.e. length of stay in Canada) has an appreciable effect on heritage Japanese. Summarizing, the multiple lines of evidence emerging from the empirical quantitative analyses of the variables targeted in this dissertation converge in indicating that heritage Japanese, as spoken in Canada, broadly shares the same underlying grammar as homeland Japanese. Structural affinities in variable patterning shared by heritage and homeland varieties reveal little compelling evidence indicating that heritage Japanese exhibits structural change due to contact with English.
Keywords: Language Contact; Japanese; Heritage Language; Sociolinguistics